Faktor Yang Berhubungan Dengan Keluhan Sick Building Syndrome Pada Pegawai - Marvita; Sunarsieh; Yuyun Tri Wahyuni; Abdul Syukur; Sriani; Juliani Saputri (Buletin Keslingmas, 2026)
Sick Building Syndrome (SBS) is a health complaint that arises when a person works in a building. When he left the building, the complaint disappeared. SBS complaints often result from environmental conditions in the building (physical, chemical, biological, and psychological factors) that are not adequately controlled and can cause financial losses. The purpose of the study was to analyze factors related to SBS complaints in Management Section Employees at Bhayangkara Anton Soedjarwo Pontianak Hospital. The type of research is observational analytics with a quantitative approach and a cross-sectional research design. The research population comprised all employees of the Management Section at Bhayangkara Anton Soedjarwo Hospital, Pontianak, totaling 62 employees, and the research sample comprised 54 people. The techniques and procedures for data collection are through physical environment measurement and filling out questionnaires. Data analysis was carried out univariately, namely, bivariate analysis using the chi-square test and multivariate analysis using logistic regression. The results of the chi-square analysis showed that there was a significant relationship between individual characteristic factors (gender) and work environment factors (temperature, humidity, lighting), and SBS complaints. The results of the analysis showed that the lighting variable had a high risk. In conclusion, there is a relationship between gender, temperature, and lighting with SBS complaints in Management Section Employees at Bhayangkara Anton Soedjarwo Pontianak Hospital, and the strongest relationship with SBS complaints is the gender variable.